2018
DOI: 10.1063/1.5032207
|View full text |Cite
|
Sign up to set email alerts
|

Saltwater transport through pristine and positively charged graphene membranes

Abstract: Transport of saltwater through pristine and positively charged single-layer graphene nanoporous membranes is investigated using molecular dynamics simulations. Pressure-driven flows are induced by motion of specular reflecting boundaries at feed and permeate sides with constant speed. Unlike previous studies in the literature, this method induces a desired flow rate and calculates the resulting pressure difference in the reservoirs. Due to the hexagonal structure of graphene, the hydraulic diameters of nano-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…It is observed that the local number density fluctuates near the NPGM, which is commonly known as density layering. This has been reported by many other researchers in MD simulations of nanofluidic flows 32,39,46,48,63 and has been authenticated experimentally. 64−66 This density layering diminishes at an approximately 3σ C−Ar distance from the NPGM, consistent with other researchers' findings.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It is observed that the local number density fluctuates near the NPGM, which is commonly known as density layering. This has been reported by many other researchers in MD simulations of nanofluidic flows 32,39,46,48,63 and has been authenticated experimentally. 64−66 This density layering diminishes at an approximately 3σ C−Ar distance from the NPGM, consistent with other researchers' findings.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…This phenomenon happens for both side reservoirs, which has also been confirmed by other researchers. 39,43,69,70 The bulk pressure (P bulk ) of each side of the membrane was calculated by averaging the local pressures in the bulk region. The bulk pressure drop (ΔP bulk ) was obtained by…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(c). The method has been widely used [7][8][9][10][11][12]. The shear-driven and force-driven flows are enabled by setting the wall a velocity of 50 nm/ns and by setting gravity of 49 m/s 2 .…”
Section: Simulation Model and Theoretical Backgroundmentioning
confidence: 99%
“…Liquid transport in nanoscale confinements is of great importance in various applications, ranging from drug delivery 1 to water desalination [2][3][4][5] and biosensing. 6 As the size of a conduit decreases down to the nanoscale, interfacial phenomena between liquid molecules and wall atoms become prominent, which leads to deviations from classical no-slip boundary conditions.…”
Section: Introductionmentioning
confidence: 99%